Rainfall Conditions When Maden Julian Oscillation Strong and Weak: Temporal Distribution in Jakarta, Bogor, and Tangerang - Wibowo, Ofana Tri; Afghani, Fadhli Aslama; Christofelts, John Pieter; Halawa, Jordana Christian (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
The Indonesian Maritime Continent has high rainfall variability with one of the causes, namely the Madden Julian Oscillation (MJO), especially in phases 3, 4, and 5. Madden Julian Oscillation (MJO) and rainfall have a correlation with one another. Therefore, this study aims to determine the effect of MJO on rainfall conditions in terms of intensity and frequency of occurrence every three months from 2013-2022 in Jakarta, Bogor, and Tangerang. The research method used is descriptive statistical analysis in the form of quarterly rainfall averages and anomalies as well as the Pearson correlation test. The data used is daily rainfall data for the 2013-2022 period. The results of the descriptive analysis show that the highest average rainfall occurs in the DJF period and the lowest is in the JJA period with the anomalies occurring in the DJF and JJA periods. On the other hand, the lowest frequency of strong and weak MJO events occurs during JJA, while the highest occurs during the DJF period. The correlation test conducted between the Madden Julian Oscillation (MJO) and rainfall found that the highest positive correlation value was 0.197073 on MAM and the highest negative correlation on SON was -0.11866, so the relationship is weak.